EFEKTIVITAS PELAKSANAAN PROGRAM GERAKAN DESA MEMBANGUN (GERDEMA) DI DESA PULAU SAPI KECAMATAN MENTARANG KABUPATEN MALINAU - Fatah Dwi Priyono (Magister Administrasi Publik FISIP Universitas Mulawarman, 2020)
The purpose of this study is to determine the effectiveness of the implementation of the village movement program (Gerdema) in the Village Island Cow District Mentarang Malinau District. This research method using explorative method with inductive approach. To obtain data of the researcher using data source in the form of person, place, and paper. Data collection techniques that the author uses are observation, interviews, and documentation. To answer and express the problems to the phenomenon that occurs the researcher uses data analysis in the form of data reduction, data presentation, and data verification. The result of the research shows that the implementation of Gerdema program in Cow Village Village of Mentarang Sub-district is not yet fully effective. It can be seen from the effectiveness indicator that is obtained by the researcher that is the success of the program, the success of the target, the satisfaction of the program, the level of input and output, and the achievement of the objective still not enough. Keywords: Effectiveness, Policy, Gerdema